Developing Tiktok Learning Videos as Instructional Media to Engage Students’ Speaking Skills - Sri Ajeng Jatry Ningsih; Yohanes Gatot Sutapa Yuliana; Ikhsanudin Ikhsanudin (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2023)
Currently, social media usage and education are tightly connected. However, teachers and students are still exposed to new obstacles as the situation changes. In the preliminary study, the researcher discovered that one of the issues was the lack of student engagement while using technology in learning speaking through online learning. Thus, the aim of this study is to develop a TikTok as instructional videos for SMPN 3 Singkawang in order to engage their speaking skills. The design of this study is a research and development design that applies ADDIE work procedures (Analysis, Design, Development or Production, Implementation or delivery, and Evaluation). The participants of the research were an English teacher and 30 junior high school students in SMPN 3 Singkawang. Qualitative data were collected from pre-observation during online classes, semi-structured interviews, and observation. On the other hand, quantitative data were collected from questionnaires as needed analysis, expert judgment, and observation sheets in the implementation phase that used the Likert scale percentage. The material expert got 55 points from 60/93.75%, categorized as very good, the Media expert got 75 from 80/91.66%, categorized as Very good. The score from the observation sheet results in the implementation stage is 89,58% which indicated that the media is in a very good category to use as a learning tool to engage speaking skills. Thus, Tiktok instructional videos have proven that it could engage students’ speaking skills.